Mycoplasma genitalium Infection Is Associated with Microscopic Signs of Cervical Inflammation in Liquid Cytology Specimens - Dehon, Patricia M.; McGowin, Chris L. (Journal of clinical microbiology, 2014)
Cervicitis is a common clinical finding often attributed to sexually transmitted infections (STIs), but no etiologic agent is identified in the majority of cases. In this study, we comparatively assessed inflammation among the common infectious etiologies of cervicitis and assessed the potential value of liquid cytology specimens for predicting STIs. Among 473 Louisiana women at low risk for acquiring STIs, the prevalences of Mycoplasma genitalium , Chlamydia trachomatis , Neisseria gonorrhoeae , and Trichomonas vaginalis in liquid-based cytology specimens were 1.5, 2.1, 0.6, and 4.4%, respectively. N. gonorrhoeae and human papillomavirus 18 (HPV18) infections were significantly more common among subjects infected with M. genitalium . Using direct microscopy, we observed significant increases in leukocyte infiltrates among subjects with monoinfections with M. genitalium or C. trachomatis compared to women with no detectable STIs. Inflammation was highest among subjects with M. genitalium . Using a threshold of ≥2 leukocytes per epithelial cell per high-powered field, the positive predictive values for M. genitalium , C. trachomatis , N. gonorrhoeae , and T. vaginalis were 100, 70, 67, and 20%, respectively. Several novel M. genitalium genotypes were identified, all of which were predicted to be susceptible to macrolide antibiotics, suggesting that different strains may circulate among low-risk women and that macrolide resistance is substantially lower than in high-risk populations. This study highlights the capacity of M. genitalium to elicit cervical inflammation and, considering the strong epidemiologic associations between M. genitalium and human immunodeficiency virus (HIV), provides a potential mechanism for acquisition and shedding of HIV via chronic leukocyte recruitment to the cervical mucosa.